Analisis Online Disinhibition Effect pada Perilaku Mahasiswa Jurusan Bimbingan dan Konseling di Media Sosial X: An Analysis of the Online Disinhibition Effect on Guidance and Counseling Students' Behavior on Social Media X - Nur Amalia Putri; Ali Rachman; Muhammad Andri Setiawan (ITScience (Information Technology and Science), 2025)
Social media X has become a space for students to interact and express their thoughts, feelings, and opinions relatively freely. This condition may give rise to the Online Disinhibition Effect (ODE), namely the tendency for individuals to exhibit more open, impulsive, or less controlled behavior online than in face-to-face interactions. This phenomenon is important to study among Guidance and Counseling (BK) students, who are required to demonstrate communication ethics, self-control, and professionalism across various interaction contexts. This study aims to analyze the Online Disinhibition Effect on the behavior of Guidance and Counseling students at Lambung Mangkurat University on social media X. This study used a quantitative descriptive method. The research sample consisted of 164 students from the classes of 2022, 2023, and 2024, selected via simple random sampling from a population of 279 students. Data were collected using a five-point Likert-scale questionnaire compiled from the six aspects of ODE, as outlined by Suler, and divided into benign and toxic disinhibition. The research instrument was deemed valid, comprising 30 statements, and demonstrated high reliability (Cronbach's Alpha = 0.940). Data analysis was conducted using descriptive statistics. The results showed that students' Online Disinhibition Effect was in the high range, with a tendency toward benign disinhibition over toxic disinhibition. The aspects of solipsistic introjection and dissociative imagination were the most prominent indicators. These findings provide an empirical contribution to the study of BK students' online behavior and have practical implications for the development of Guidance and Counseling education, particularly by strengthening digital literacy, online communication ethics, and the self-regulation of prospective counselors.